Short interpregnancy interval can lead to adverse pregnancy outcomes: A meta-analysis - Wang, Yumei; Zeng, Can; Chen, Yuhong; Yang, Liu; Tian, Di; Liu, Xinghui; Lin, Yonghong (Frontiers in Medicine, 2022)
Background The evidence of some previous papers was insufficient in studying the causal association between interpregnancy interval (IPI) and adverse pregnancy outcomes. In addition, more literature have been updated worldwide during the last 10 years. Methods English and Chinese articles published from January 1980 to August 2021 in the databases of PubMed, Cochrane Library, Ovid, Embase, China Biology Medicine disc (CBM), and China National Knowledge Infrastructure (CNKI) were searched. Then following the inclusion and exclusion criteria, we screened the articles. Utilizing the Newcastle–Ottawa Scale (NOS), we evaluated the quality of the included articles. The literature information extraction table was set up in Excel, and the meta-analysis was performed with Stata 16.0 software (Texas, USA). Results A total of 41 articles were included in the meta-analysis, and NOS scores were four to eight. The short IPI after delivery was the risk factor of preterm birth (pooled odds ratio 1.49, 95% confidence interval 1.42–1.57), very preterm birth (pooled OR: 1.82, 95% CI: 1.55–2.14), low birth weight (pooled OR: 1.33, 95% CI: 1.24–1.43), and small for gestational age (pooled OR: 1.14, 95% CI: 1.07–1.21), offspring death (pooled OR: 1.60, 95% CI: 1.51–1.69), NICU (pooled OR: 1.26, 95% CI: 1.01–1.57), and congenital abnormality (pooled OR: 1.10, 95% CI: 1.05–1.16), while was not the risk factor of gestational hypertension (pooled OR: 0.95, 95% CI: 0.93–0.98) or gestational diabetes (pooled OR: 1.06, 95% CI: 0.93–1.20). Conclusion Short IPI (IPI < 6 months) can lead to adverse perinatal outcomes, while it is not a risk factor for gestational diabetes and gestational hypertension. Therefore, more high-quality studies covering more comprehensive indicators of maternal and perinatal pregnancy outcomes are needed to ameliorate the pregnancy policy for women of childbearing age.